Cardiac resynchronization - a modern method of chronic heart failure treatment - V. S. Nikiforov; M. B. Didenko; G. G. Khubulava; A. S. Svistov (Российский кардиологический журнал)
Pathogenetic mechanisms of inter- and intraventricular synchronism influence on chronic heart failure (CHF) progression, as well as cardiac resynchronization (CR) mechanisms, are discussed. CH indications, based on multicenter trials' results, are presented. CR technique and methods ofCR effectiveness assessment are described. CR beneficial effects on clinical status and prognosis in CHF patients are emphasized.